#exstrange: Curatorial Interventions on eBay. (1st April 2017) - Ghidini, Marialaura
#exstrange (2017) was an online curatorial project in which artworks were displayed and sold, auction-style, on eBay. For three months in 2017, the project presented one artwork-as-auction per day to interrogate the functioning of this e-commerce platform and the role of digital culture in everyday life. By focusing on the interactivity and global networking of the Internet, #exstrange sought to reconsider the relationship between exhibitions, artworks and audiences.